STRESS-INDUCED GLIAL HISTOPATHOLOGY AS A MEDIATOR OF NEUROPSYCHIATRIC VULNERABILITY: INSIGHTS FROM RODENT AND ZEBRAFISH MODELS - Cahayani, Wike Astrid (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction – Glial cells, including astrocytes, microglia, and oligodendrocytes, are active regulators of neural plasticity, synaptic integrity, and connectivity. Chronic and early-life stress are major risk factors for neuropsychiatric disorders, yet the role of glial histopathology in mediating this vulnerability remains incompletely understood. This thematic narrative review aims to synthesize integrative evidence on stress-induced glial histopathology as a mediator of neuropsychiatric risk, with emphasis on findings from rodent and zebrafish models and their translational implications. Methods – A structured thematic narrative review was conducted across PubMed, Scopus, and Embase for studies published between 2000 and 2025. Inclusion criteria prioritized high-quality experimental research and reviews on glial responses to stress, synaptic alterations, and biomarker potential in rodent and zebrafish models. Results – Evidence consistently demonstrates astrocyte atrophy, microglial activation with pro-inflammatory profiles, and oligodendrocyte dysfunction leading to myelin disruption, collectively contributing to synaptic instability, neuroinflammation, and impaired connectivity. Discuss – Rodent models provide detailed insights into cellular and regional pathology, while zebrafish models offer translational value through high-throughput behavioral and neuroimmune profiling. Species differences in glial structure and stress responsiveness remain a barrier to direct clinical translation. Conclusion – Glial pathology represents a unifying mechanism linking stress exposure to neuropsychiatric vulnerability. Future studies should integrate cross-species, longitudinal designs and translational biomarkers to advance therapeutic strategies for stress-related mental health disorders.